Learning Strategies For Children Special Needs - Anisa Julia Prawesti; Bayu Septian Anuraga; Rio Setya Budi Nugraha (Proceedings of The ICECRS, 2020)
This study aims to determine the Learning Strategies For Children Special Needs. The method used in this research is the study of literature. This research produces educational services for individuals with special needs is inclusive education by deepening the application of learning strategies for children with special needs.